2011
DOI: 10.1186/1471-2148-11-368
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of positive selection in Toll-like receptor (TLR) genes in mammals

Abstract: BackgroundToll-like receptors (TLRs) are a major class of pattern recognition receptors (PRRs) expressed in the cell surface or membrane compartments of immune and non-immune cells. TLRs are encoded by a multigene family and represent the first line of defense against pathogens by detecting foreigner microbial molecular motifs, the pathogen-associated molecular patterns (PAMPs). TLRs are also important by triggering the adaptive immunity in vertebrates. They are characterized by the presence of leucine-rich re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
171
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(204 citation statements)
references
References 82 publications
(135 reference statements)
24
171
1
1
Order By: Relevance
“…No positive selection signatures were detected in the intracellular TIR domain, which suggests that positive selection acts mainly on ligand-binding regions. This confirms the results of similar analyses undertaken on mammals [7,9,10,88,89] and amniotes [22]. Projection of positively selected and functionally important sites onto 3D protein models of GaGaTLR revealed changes at six positions (TLR4: 343; TLR5: 180, 209, 342, 379; TLR7: 26) that could directly influence receptor expression or function (Figures 2, 3 and 4, see Additional file 1: Tables S7 and S8 and Additional file 3: Section S4).…”
Section: Resultssupporting
confidence: 91%
“…No positive selection signatures were detected in the intracellular TIR domain, which suggests that positive selection acts mainly on ligand-binding regions. This confirms the results of similar analyses undertaken on mammals [7,9,10,88,89] and amniotes [22]. Projection of positively selected and functionally important sites onto 3D protein models of GaGaTLR revealed changes at six positions (TLR4: 343; TLR5: 180, 209, 342, 379; TLR7: 26) that could directly influence receptor expression or function (Figures 2, 3 and 4, see Additional file 1: Tables S7 and S8 and Additional file 3: Section S4).…”
Section: Resultssupporting
confidence: 91%
“…For a more conservative approach, and as used previously, 43,44 only sites detected to be under positive selection in more than one ML method were considered. Alterations in coding regions of genes that lead to amino acids substitutions can induce changes in protein conformation.…”
Section: Codon-based Analyses Of Positive Selectionmentioning
confidence: 99%
“…The phylogram showed that in B. mori, Toll had evolved at a later stage of evolution presumably due to slow but accumulated demand (77% varied amino acids and six replacements; Table 3) by pathogen invasion to activate immune responses which is a recent adaptation in holometabolous insects [56,80,81]. Thus the BmToll is under strong evolutionary pressure by infections in different higher organisms including human beings [56,82,83].…”
Section: Phylogenetic Analysismentioning
confidence: 99%